2012
DOI: 10.1007/s10068-012-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nuruk and fermentation method on organic acid and volatile compounds in brown rice vinegar

Abstract: The effects of different nuruk contents and fermentation methods (AV, vinegar fermented in an agitated culture; SV, vinegar fermented in a static culture) on organic acids and volatile compounds in brown rice vinegars were investigated. In the SV, the contents of acetic, oxalic, tartaric, and malic acids increased with hipher contents of nuruk. Acetic, tartaric, and malic acid contents were higher in the SV than those in the AV. Volatile compounds that can affect vinegar quality, including acetic acid, isoamyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The occurrences of acetic, lactic, citric, malic, pyruvic and succinic acid in 58 samples of lager beers, representing 20 different brands from different parts of the world, have also been reported by Nord et al (26). Lee et al (27) found that a static fermentation of brown rice produced a high content of acetic, oxalic, tartaric and malic acids with increasing concentrations of the starter Nuruk. They also found that the acetic, tartaric and malic acid contents were higher in static cultures compared with agitated cultures.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The occurrences of acetic, lactic, citric, malic, pyruvic and succinic acid in 58 samples of lager beers, representing 20 different brands from different parts of the world, have also been reported by Nord et al (26). Lee et al (27) found that a static fermentation of brown rice produced a high content of acetic, oxalic, tartaric and malic acids with increasing concentrations of the starter Nuruk. They also found that the acetic, tartaric and malic acid contents were higher in static cultures compared with agitated cultures.…”
Section: Discussionmentioning
confidence: 62%
“…Lee et al . found that a static fermentation of brown rice produced a high content of acetic, oxalic, tartaric and malic acids with increasing concentrations of the starter Nuruk . They also found that the acetic, tartaric and malic acid contents were higher in static cultures compared with agitated cultures.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have demonstrated that amino acids enhance the taste of food (Kong et al., ) and play a critical role in the growth and development of human body (Sun et al., ). Meanwhile, organic acids derived from fermentation and minors are from the raw material, which can influence the flavor of vinegars (Lee et al., ). Among all organic acids, lactic acid is produced by proliferating lactic acid bacteria at the beginning of alcoholic fermentation and acetic acid is generated from oxidizing alcohol during the acetic acid fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Acetic acid, lactic acid, citric acid, and phenolic compounds are considered important compounds that contribute to the aromatic quality of vinegar, and volatile components of vinegar have been used to distinguish between quality and defective or adulterated samples of vinegar Lee et al 2012). Moreover, thanks to special compounds responsible for the functions of vinegar, various types of vinegars can be differentiated by the discrepancy in the contents of compounds (Del Signore 2001).…”
Section: The Relationship Between Compounds and Functionality Of Vinegarmentioning
confidence: 99%
“…For example, in fruit vinegar production, the occurrence of AF coincides with saccharification because no distinct saccharification step exists in fermentation. By contrast, some rice and cereal vinegars that are produced with starchy raw materials have a distinct saccharification step (Haruta et al 2006;Lee et al 2012). However, AF and AAF are distinctly different and have separate biochemical processes, and both are the results of the action of microorganisms.…”
Section: Introductionmentioning
confidence: 99%